Age and Sex Comparisons in Pediatric Track and Field Hurdle Injuries Seen in Emergency Departments of the US - Jacob Jones; Luke Radel; Kyle Garcia; David Soma; Shane Miller; Dai Sugimoto (MDPI AG, 2023)
There is limited literature analyzing pediatric hurdle injuries based on sex and age. This study compares hurdle-related injury types, injured body parts, and injury mechanisms by age and sex in pediatrics. Hurdle-related injury data from the National Electronic Injury Surveillance System were used to retrospectively review the injuries of hurdlers 18 years and under. Differences in injured body parts, injury types, and mechanisms were analyzed by age (pre-high school vs. high school) and sex (male vs. female). A total of 749 cases were extracted. Fractures were more common in pre-high schoolers (34.1% vs. 21.5%, p = 0.001), while more sprains were identified in high schoolers (29.6%) than pre-high schoolers (22.8%, p = 0.036). Males suffered more fractures than females (35.1% vs. 24.3%, p = 0.001). Females sustained more joint sprains (29.1% vs. 21.0%, p = 0.012) and contusions/hematomas (12.7% vs. 7.5%, p = 0.020). Ankle injuries were more common in females (24.0%) than males (12.0%, p = 0.001), while wrist injuries were more prevalent in males (11.7% vs. 7.2%, p = 0.034). The most common injury mechanism was apparatus-related, with no differences based on age or sex. Injury types and injured body parts differed depending on age and sex in pediatric hurdle injuries seen in emergency departments. These findings may be helpful for injury prevention and medical care for pediatric hurdlers.